2016
DOI: 10.1089/zeb.2016.1303
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein Requirement During Juvenile Growth of Zebrafish (Danio rerio)

Abstract: A standard diet for zebrafish, based on their specific nutritional requirements, is of primary importance to improve experimental outcomes with this model organism and optimize its large-scale production. However, the main basic nutritional requirements of zebrafish are yet to be determined. This study aimed at contributing to fill this gap by evaluating the dietary protein requirement of zebrafish juvenile. Ten isoenergetic fishmeal-based diets with increasing protein levels (15%-60%) were formulated, and eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
30
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 33 publications
10
30
4
Order By: Relevance
“…However, since the right side of the curve did not display a clear descending trend, a great caution should be exercised before a definite conclusion is reached in terms of inhibition level of dietary protein. The descending trend at the right side of SGRs curve is inconsistent with previous observations in zebrafish (Fernandes et al 2016;O'Brine et al 2015), who found a plateau at high protein levels. We can conclude that our SGR data appears to be suitable for estimation of only minimum dietary protein using the TBPLM model level but not for the inhibition level.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, since the right side of the curve did not display a clear descending trend, a great caution should be exercised before a definite conclusion is reached in terms of inhibition level of dietary protein. The descending trend at the right side of SGRs curve is inconsistent with previous observations in zebrafish (Fernandes et al 2016;O'Brine et al 2015), who found a plateau at high protein levels. We can conclude that our SGR data appears to be suitable for estimation of only minimum dietary protein using the TBPLM model level but not for the inhibition level.…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with the results reported by Akpιnar et al (2012) and Fernandes et al (2016), who observed an inverse relation between feed intake and dietary protein in juvenile shi drum (Umbrina cirrosa) and zebrafish. This phenomenon could be attributed to compensatory response to get more protein in fish fed lower dietary protein levels, as argued by several authors (Akpιnar et al 2012;El-Dakar et al 2011;Fernandes et al 2016;O'Brine et al 2015). Therefore, at restricted feeding regimes at the estimated requirement level in this study fish may not meet their daily protein requirements and significant attention should be paid to feeding levels in zebrafish laboratories.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations